Effect Of Service Quality And Company Image On Customer Loyalty - A.A. Ketut JAYAWARSA; A.A. Sri PURNAMI; Kadek Novita Maharani DEWI (Indonesia Strategic Sustainability, 2021)
This study is entitled The Effect of Service Quality and Company Image on Customer Loyalty at PT. BPR Sari Jaya Sedana in Klungkung. The formulation of the problem is: How is the influence of service quality and company image on customer loyalty simultaneously and partially at BPR Sari Jaya Sedana. The objectives of this study were: To determine the effect of service quality and corporate image on customer loyalty simultaneously and partially at BPR Sari Jaya Sedana. The sample which is the object of this research is the customer at PT. BPR Sari Jaya Sedana. The sampling technique used random sampling technique with data collection techniques in the form of questionnaires with respondents as many as 40 customers. The data analysis technique used is the validity and reliability test, the classical assumption test, the determination test, the f test, and the t-test with multiple linear regression methods. The results showed that service quality and company image had a significant positive effect on customer loyalty. Then partially, service quality and company image also have a significant positive effect on customer loyalty.